WAWASAN GENDER DALAM PROSES PENCIPTAAN MANUSIA (STUDI KOMPARATIF PEMIKIRAN RASYID RIDHA, AMINAH WADUD DAN RIFFAT HASAN) - Nurfanita, Sania; Sugiarto, Fitrah (Universitas Al-Amien Prenduan, 2023)
This journal examines the thoughts of Islamic reformers who are modern Muslim commentators and feminist figures about the origin of human creation. Including what is contained in it, namely how the concept of gender is a controversial topic among Islamic leaders and muslim feminists. Feminists claim that there is an element of discrimination against women in the interpretation of the classical mufassir where in every verse related to gender, they seem to elevate the degree of men compared to women. In fact, Islam is not such a religion. islam is a just religion, equating the degrees of men and women. With this discriminatory interpretation, feminists believe that it is necessary to reinterpret gender-insightful verses of the Qur'an so that the concept of justice in Islam is immediately revealed. The research method in this journal is a comparative method based on literature studies. The results of this study will reveal the concept of nafs wahidah and zauj in surah An-Nisa Verse 1 and Az-Zumar (39): 6 which is the key to the analysis of gender issues faced.